A simple and industrially scalable method for making a PANI-modified cellulose touch sensor. (15th February 2021) - Ragazzini, I.; Gualandi, I.; Selli, S.; Polizzi, C.; Cassani, M.C.; Nanni, D.; Gambassi, F.; Tarterini, F.; Tonelli, D.; Scavetta, E.; Ballarin, B.
Graphical abstract: Highlights: Preparation of highly conductive polyaniline-coated cellulose sheets. Fabrication of capacitive touch sensors via a simple, inexpensive and robust method. Scalable industrial process for paper-based touch sensors. Easy touch sensor sensibility modulation through tailor-made geometry. Abstract: In this work we present a simple, inexpensive, and easily scalable industrial paper process to prepare sheets of conductive cellulose fibers coated with polyanilines. First, bare fibers were coated by in situ oxidative polymerization of polyaniline then, the resulting composite fibers were used to fabricate electroactive sheets. The resistivity of the sheets is 14 ± 1 Ω sq −1, a value around 1000 times lower than those reported in literature. The superior electronic proprieties of the sheets were demonstrated by assembling a capacitive touch sensor device with optimized geometry. The touch sensor shows an increase of 3–4 % of the starting electric capacity after compression and a fast response time of 52 ms. To our knowledge this is the first time that a device is prepared in this way and therefore, the herein presented results can bring an significant improvement in the development of low-cost, green and high-tech electronic devices.